Regulation of endothelial intracellular adenosine via adenosine kinase epigenetically modulates vascular inflammation - Xu, Yiming (Nat Commun, 2017)
The molecular mechanisms underlying vascular inflammation and associated inflammatory vascular diseases are not well defined. Here we show that endothelial intracellular adenosine and its key regulator adenosine kinase (ADK) play important roles in vascular inflammation. Pro-inflammatory stimuli lead to endothelial inflammation by increasing endothelial ADK expression, reducing the level of intracellular adenosine in endothelial cells, and activating the transmethylation pathway through increasing the association of ADK with S-adenosylhomocysteine (SAH) hydrolase (SAHH). Increasing intracellular adenosine by genetic ADK knockdown or exogenous adenosine reduces activation of the transmethylation pathway and attenuates the endothelial inflammatory response. In addition, loss of endothelial ADK in mice leads to reduced atherosclerosis and affords protection against ischemia/reperfusion injury of the cerebral cortex. Taken together, these results demonstrate that intracellular adenosine, which is controlled by the key molecular regulator ADK, influences endothelial inflammation and vascular inflammatory diseases.